Model for Evaluation of the Economic-Social-Environmental Outcomes of Investments in Road Transport Infrastructure - Kozłowski, Waldemar (Olsztyn Economic Journal, 2012)
This paper presents a model for valuation of the economic-social benefits and costs of investments in road transport infrastructure. The analysis of benefits and costs was based on three research areas: economic, social and environmental. Currently, the valuation of benefits and costs resulting from investments in road infrastructure is increasing in importance from the perspective of local development assigning a special role to road investments. Modernisation of road infrastructure has an indirect influence on the economic development of municipalities in the form of so-called economic-social-environmental outcomes that are of both a direct and indirect nature.